The book of goose eaudiobook A novel. - Li, Yiyun (Macmillan Audio, 2022)
A magnificent, beguiling tale winding from the postwar rural provinces to Paris, from an English boarding school, to the quiet Pennsylvania home where a woman can live without her past, The Book of Goose is a story of disturbing intimacy and obsession, of exploitation and strength of will, by the celebrated author Yiyun Li. Fabienne is dead. Her childhood best friend, Agnès, receives the news in America, far from the French countryside where the two girls were raised—the place that Fabienne helped Agnès escape ten years ago. Now, Agnès is free to tell her story. As children in a war-ravaged, backwater town, they'd built a private world, invisible to everyone but themselves—until Fabienne hatched the plan that would change everything, launching Agnès on an epic trajectory through fame, fortune, and terrible loss. A Macmillan Audio production from Farrar, Straus and Giroux.